A A Low-Cost MQTT-Based IoT Framework for Real-Time Monitoring of Battery Energy Storage Systems - Ari Hasan Asyari; Irsyad Nashirul Haq; Rina Mardiati (Universitas Andalas, 2026)
Electricity consumption continues to increase in line with population growth and the rising demand for energy. However, this trend is inversely proportional to the availability of electrical energy resources, particularly those supporting clean energy. One of the renewable energy sources is solar power generation, which utilizes solar radiation. In practice, solar power systems cannot operate optimally under cloudy conditions or during nighttime. Therefore, a Battery Energy Storage System (BESS) plays a crucial role in providing a reliable and continuous energy supply over a certain period. In addition, BESS requires proper monitoring to assess its operational condition. This study presents the development of an IoT-based real-time monitoring system for BESS using the MQTT communication protocol. An ESP32 module is employed as the internet gateway (publisher), while a cloud-based compute engine functions as the subscriber. The proposed system enables real-time monitoring of key parameters, including voltage, current, power, temperature, as well as battery charging and discharging states, which are stored and visualized in a cloud database. The results demonstrate that the developed prototype is capable of publishing and subscribing energy storage data effectively, with a sensor accuracy error of approximately 1%. The overall system achieves an average response time of 1.41 seconds, indicating reliable real-time performance.